Sildenafil for Pulmonary Arterial Hypertension. (July 2019) - Bhogal, Sukhdeep; Khraisha, Ola; Al Madani, Mohammad; Treece, Jennifer; Baumrucker, Steven J.; Paul, Timir K.
Abstract : Pulmonary hypertension is a life-threatening illness with debilitating physical and emotional consequences. The progression of this devastating disease is characterized by a continuous increase in pulmonary vascular resistance, which results in elevated pulmonary artery pressure and leads to right heart failure. Treatment is focused on targeting the underlying complex etiology via the endothelin, prostacyclin, and nitric oxide (NO) pathways. Emergence of new treatments over the past 2 decades has led to improvement in the functional status and time to clinical worsening. Even with recent advances, outcomes remain suboptimal. Phosphodiesterase-5 (PDE-5) inhibitors, such as sildenafil, were approved for treatment of pulmonary arterial hypertension (PAH) by the Food and Drug Administration (FDA) in 2005, which holds promise in improving quality of life and therefore making this class of medications effective palliative therapy agents. In this review, we summarize the emergence of sildenafil as a treatment for PAH and its role as palliative therapy.